2013
DOI: 10.1007/s00726-013-1639-1
|View full text |Cite
|
Sign up to set email alerts
|

Se-(2-aminoalkyl)selenocysteines as biochemical redox agents. A tool to contrast cell injury induced by aflatoxin B1 in HepG2 cells

Abstract: Se-(2-aminoalkyl)selenocysteines were shown to have a chemoprotective activity towards HepG2 cells, contrasting the cell damage of aflatoxin B1. The results of this study suggest that our newly synthesized seleno-diamino acids are apparently endowed with a potent protective potential against cell damage caused by AFB1 similar to, or even higher than, that exerted by the reference compound Se-Me-SeCys. The protective effect does not seem to be absolute, i.e., merely determined by the presence of the chalcogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The treatments with the mycotoxins lasted up to 24 h, depending on the experiment. The range of mycotoxin concentrations were selected on the basis of literature data (maximum permissible levels and intestinal absorption in rats) and our previous studies performed on hepatic cell lines and splenocytes from rat (Abdel Nour et al, 2007;Chuturgoon et al, 2014;Ehrlich et al, 2002;Liu et al, 2012;Lv et al, 2014;Hanioka et al, 2012;Mary et al, 2012;Nucci et al, 2014;Theumer et al, 2010Theumer et al, , 2003Theumer et al, , 2002. The lower cytotoxicity observed in the CALUX cells allowed the application of higher concentrations in order to observe any possible effects, and as a consequence, the range of concentrations used for the CALUX and for the EROD assays were different.…”
Section: Cell Exposurementioning
confidence: 99%
“…The treatments with the mycotoxins lasted up to 24 h, depending on the experiment. The range of mycotoxin concentrations were selected on the basis of literature data (maximum permissible levels and intestinal absorption in rats) and our previous studies performed on hepatic cell lines and splenocytes from rat (Abdel Nour et al, 2007;Chuturgoon et al, 2014;Ehrlich et al, 2002;Liu et al, 2012;Lv et al, 2014;Hanioka et al, 2012;Mary et al, 2012;Nucci et al, 2014;Theumer et al, 2010Theumer et al, , 2003Theumer et al, , 2002. The lower cytotoxicity observed in the CALUX cells allowed the application of higher concentrations in order to observe any possible effects, and as a consequence, the range of concentrations used for the CALUX and for the EROD assays were different.…”
Section: Cell Exposurementioning
confidence: 99%
“…To this purpose we utilized two members of a family of compounds characterized by the presence of selenium in their amino acidic aromatic rings. The biological properties of these compounds, whose anti-oxidant activities were already documented, have been previously described [27]. In particular, we utilized SeMC, as a reference commercial compound, and SeDA4, as a newly in-house synthesized compound.…”
Section: Resultsmentioning
confidence: 99%
“…Se-(Methyl)selenocysteine hydrochloride (SeMC, M6680), the oxidant-sensitive dye 2′,7′-dichlorofluorescin diacetate (DCFH-DA, D6883), H 2 O 2 (H1009) and cycloheximide (CHX, 01810) were purchased from Sigma-Aldrich (St. Louis, MO, USA). A second selenium-based compound used in this study and identified as Seleno-Diamino Acid 4 (SeDA4), is a synthetic molecule obtained and characterized for its anti-oxidant and biological properties as previously described [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This action reduces the symmetry and makes distortion on the metallic cluster as well as their isomers and of course changes the properties of the whole materials. Proton and ( 1 H) carbon ( 13 C) NMR of complex protein molecules were employed to investigate Se-(2-aminoalkyl)selenocysteines as biochemical redox agents [63]. In this case, chalcogen-biochemical substance was investigated through the behavior of its protons and carbons.…”
Section: Methods For Chalcogen Materials Characterizationmentioning
confidence: 99%